Development and modern situation of methodology of science on bibliography - Янонис, Освальдас (Knygotyra, 1981)
In the articlle the development of the viewpoints of book researchers and bibliographists on methodology of the bibliographycal science in the Soviet period is considered. On this development is based the increase of the value of methodology in the modern times. In the article the definition of this methodology is given and the problems of the methodology of science on bibliography enumerated.